Meningkatkan Aktivitas dan Hasil Belajar IPA Menggunakan Alat Peraga Science Education Quality Improvement Project (Seqip) Siswa Kelas IV SD Negeri 3 Sripendowo Lampung Timur TP 2019/2020 - Sukamti, Sukamti (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
Fourth grade students at SDN 3 Sripendowo in studying science have not achieved completeness, this can be seen from student learning outcomes so far have not reached the Minimum Completeness Criteria for subjects that have been set in the school curriculum. The purpose of this study was to describe the use of the Science Education Quality Improvement Project (SEQIP) teaching aids in increasing the activities and learning outcomes of Natural Sciences in Grade IV students of SDN 3 Sripendowo, East Lampung, Odd Semesters for the 2019/2020 Academic Year. The research subjects were fourth grade students at SDN 3 Sripendowo, East Lampung. The research was carried out from September to November 2019. The results showed that the use of the Science education quality improvement project (Seqip) teaching aids could increase the activities and learning outcomes of Natural Sciences (IPA) in fourth grade students of SDN 3 Sripendowo East Lampung in the 2019/2020 academic year.